PENINGKATAN KINERJA PENJUALAN UKM BERBASIS INTELLECTUAL CAPITAL DAN INOVASI PRODUK (Studi Pada UKM Di Kota Tangerang, Provinsi Banten) - Humairoh Humairoh; Agung Budi (Universitas Muhammadiyah Tangerang, 2019)
The aims of this study are analyzing the influence of intellectual capital againts sales performace, intellectual capital againts product innovation, product Innovation againts sales performance, intellectual capital againts sales performance through product innovation as the intervening variables on SMES. The reseach type is a causal research to obtain evidences of causal relationships with a sample of 98 respondents as business owners SMES. The sampling technique used purposive sampling with questionnaires as the instrument to collect data whose result processed using method Scala Likert Summated Rating (LSR) with score 1 – 5. This research used technique of path analysis using Smart PLS. The results of this hypothesis indicated that intellectual capital has a positive and significant influence on sales performance (CR 3,558>1,96), intellectual capital has a positive and significant againts produk innovation (CR 18,450>1,96), product innovation has a positive and significant againts sales performance (CR 6,472>1,96)) and intellectual capital throuh product innovation as variable intervening againts sales performance, obtained the result of CR 31,203 (>1,96). The contribution of intellectual through product innovation againt sales performace by 85,9%. The contribution of intellectual againt product innovation by 57,9%.Keyword : Sales Performance, Product Innovation, Intellectual Capital